2008
DOI: 10.4321/s1130-01082008001100011
|View full text |Cite
|
Sign up to set email alerts
|

Linfoma hepático primario: Evolución favorable con quimioterapia combinada con rituximab

Abstract: This article describes the case of a patient with a non-Hodgkin primary hepatic lymphoma who was successfully treated with chemotherapy combined with rituximab. Using the Medical Subject Headings the published reports of this rare entity were reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
6
0
3
Order By: Relevance
“…In addition, a previous study revealed that antiviral treatment following cytotoxic treatment contributed towards a significantly increased disease-free survival period in 69 HCV-seropositive B-cell lymphoma cases (25). The use of the R-CHOP regimen has been found to increase the complete remission rate and prolong the survival significantly (17,24). These data strongly indicate that rituximab and cytotoxic treatment, followed by antiviral treatment, may result in an improved clinical outcome in primary hepatic and systemic HCV-seropositive DLBCL cases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous study revealed that antiviral treatment following cytotoxic treatment contributed towards a significantly increased disease-free survival period in 69 HCV-seropositive B-cell lymphoma cases (25). The use of the R-CHOP regimen has been found to increase the complete remission rate and prolong the survival significantly (17,24). These data strongly indicate that rituximab and cytotoxic treatment, followed by antiviral treatment, may result in an improved clinical outcome in primary hepatic and systemic HCV-seropositive DLBCL cases.…”
Section: Discussionmentioning
confidence: 99%
“…R-CHOP is used for CD20 + tumors. [17][18][19][20][21] Surgery is indicated for localized disease and surgical debulking before or after chemotherapy. Adjuvant chemotherapy after complete surgical resection results in complete remission of disease.…”
Section: Discussionmentioning
confidence: 99%
“…A pesar de lo infrecuente que el LH se presente con compromiso hepático importante, nuestro reporte muestra la necesidad de contar con esquemas de quimioterapia alternativos y de baja toxicidad para estos pacientes. En la literatura revisada, encontramos reportes de uso de CHOP, MOPP (mecloretamina, vincristina, procarbazina, prednisona) y DHAP con resultados positivos 4,5,13 . En la paciente del caso planteado se eligió como primera aproximación terapéutica el uso de CHOP, el que debió suspenderse por el deterioro clínico y de laboratorio tras su inicio.…”
Section: Rev Med Chile 2012; 140: 902-905unclassified
“…En la paciente del caso planteado se eligió como primera aproximación terapéutica el uso de CHOP, el que debió suspenderse por el deterioro clínico y de laboratorio tras su inicio. Esto contrasta con el caso reportado de una paciente que se presenta con compromiso hepático que fue tratada inicialmente con CHOP de manera exitosa 4 . Aunque, es importante destacar que esta paciente presentaba menor compromiso sistémico y no poseía comorbilidades, lo que nos lleva a plantear la importancia de la elección y adecuación del esquema según cada paciente.…”
Section: Rev Med Chile 2012; 140: 902-905unclassified
See 1 more Smart Citation